Journalism approach to teaching and learning communication in English - Nata o, Norberto M.; Marquez-Bayangos, Eloisa (Mandaluyong City, 2019)
Language is inevitable in communication. To communicate effectively in English language, one has to be knowledgeable on the rules of grammar. It is observed that students find it difficult in expressing themselves using our second language. Hence, it is important to enrich/to enhance the students when it comes to using the language.
Keywords: Journalism